ANALYSIS OF CREDIT TAKING PT. BPR BANK KLATEN (PERSERODA) - Afik Afik; Sudarwati Sudarwati; Ida Aryati; Afiefah Sulistyowati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study intends to analyze the effect of interest rates, the effect of service quality, the effect of collateral (collateral), and the effect of credit procedures on credit taking at PT BPR Bank Klaten (Perseroda). The research was conducted at PT BPR Bank Klaten (Perseroda) UMK Jatinom which is located at Jl. Tulung-Boyolali, Bonyokan, Jatinom (Ruko Tangkilan). This research was carried out effectively for 6 months, August to December 2021. Multiple linear regression analysis was utilized in this study to analyze the data using SPSS. Based on the result, all variables have a significant effect on the credit taking decision in PT BPR Bank Klaten (Perseroda). Keywords: Credits, Interest rate, Quality of service, Collateral